2022
DOI: 10.1371/journal.pone.0264340
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid level and all-cause and cardiovascular mortality in peritoneal dialysis patients: A systematic review and dose-response meta-analysis of cohort studies

Abstract: Background The association between serum uric acid (SUA) and all-cause and cardiovascular disease (CVD) mortality in peritoneal dialysis (PD) patients is controversial. Therefore, we aimed to determine the relationship between SUA and all-cause and CVD mortality in PD patients. Method Web of Science, EMBASE, PubMed and the Cochrane Library databases were searched from their inception to 7 April 2021. Effect estimates were presented as hazard ratios (HRs) with 95% confidence intervals (95% CIs) and pooled usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…[3][4][5] As the final enzyme product of purine metabolism, uric acid (UA) levels in serum have been associated with many diseases, 6 including metabolic syndrome, 7 diabetes mellitus, 8 dyslipidemia, 9 chronic kidney disease, 10 and liver dysfunctions. 11 Recent studies have demonstrated that serum UA levels are also associated with obesity 6,12 and are considered a predictor of cardiovascular disorders 13 including hypertension. 14,15 However, the causal linkages between the three metabolic conditions are not very clear.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] As the final enzyme product of purine metabolism, uric acid (UA) levels in serum have been associated with many diseases, 6 including metabolic syndrome, 7 diabetes mellitus, 8 dyslipidemia, 9 chronic kidney disease, 10 and liver dysfunctions. 11 Recent studies have demonstrated that serum UA levels are also associated with obesity 6,12 and are considered a predictor of cardiovascular disorders 13 including hypertension. 14,15 However, the causal linkages between the three metabolic conditions are not very clear.…”
Section: Introductionmentioning
confidence: 99%
“… 13 For example, although febuxostat and allopurinol drugs can reduce uric acid levels, they increase the risk of cardiovascular disease. 14 In order to provide more diversified treatment options for patients, we have studied the role of Chinese medicine in the treatment of gout. Tongbixiao pills were developed by the Gout TCM Research Cooperation Group of Jingzhou Hospital of Traditional Chinese Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Some traditional CVD risk factors [ 3 ] including smoking, physical activity, hypertension, diabetes, and hyperlipidemia, may contribute to poor survival outcomes among PD patients [ 4 ]. Other studies have shown that inflammatory status [ 5 , 6 ], malnutrition [ 6 9 ], electrolyte disturbance [ 10 12 ], metabolic disorder [ 13 15 ], lower plant-based protein intake [ 16 ], alkaline phosphatases [ 17 ], and older age [ 18 ] were risk factors for all-cause mortality in patients undergoing PD. These factors above, particularly inflammation, are well-known nontraditional CVD risk factors [ 3 ] and may further increase the risk of death in such populations [ 19 ].…”
Section: Introductionmentioning
confidence: 99%